1998
DOI: 10.1046/j.1365-2249.1998.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement-regulatory protein expression and activation of complement cascade on erythrocytes from patients with rheumatoid arthritis (RA)

Abstract: It has been previously reported that the expression of the complement receptor, CR1, on erythrocytes is reduced in patients with RA and that the reduced expression of CR1 is related to disease activity. In this study we investigate the role of other regulatory proteins, i.e. decay-accelerating factor (DAF) and CD59 (membrane inhibitor of reactive lysis), in the pathogenesis of RA by checking the expression of DAF and CD59 on erythrocytes of RA patients to establish whether reduced expression of DAF and CD59 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Complement activation plays a pathogenic role in human RA, as suggested by the decreased levels of decay-accelerating factor (DAF) on the erythrocytes of RA patients (76), the activated phenotype of their polymorphonuclear cells (PMN) and monocytes (76)(77)(78), and the increased levels of complement regulatory proteins the DAF (CD55) and CR1 on PMN from RA synovial fluid (79). Among the several complement control proteins prepared by molecular biologic techniques, recombinant soluble CR1 has demonstrated the Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation plays a pathogenic role in human RA, as suggested by the decreased levels of decay-accelerating factor (DAF) on the erythrocytes of RA patients (76), the activated phenotype of their polymorphonuclear cells (PMN) and monocytes (76)(77)(78), and the increased levels of complement regulatory proteins the DAF (CD55) and CR1 on PMN from RA synovial fluid (79). Among the several complement control proteins prepared by molecular biologic techniques, recombinant soluble CR1 has demonstrated the Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were reiterated in the passive K/BxN serum–transfer model (18, 19). The observation that CD55 is expressed at very high levels on fibroblast‐like synoviocytes (FLS) (20–23) has prompted speculation on its role in RA in connection with the complement system (24, 25).…”
mentioning
confidence: 99%
“…This was doubted by the experimental evidence, since Arora et al observed no alteration in the expression of DAF and MIRL after incubating normal erythrocytes with RA patient sera whose RBCs exhibited significantly diminished expression of CD55 and CD59 [67]. In addition, the authors proposed as the cause, the spontaneous vesiculation that occurred to erythrocytes incubated with MAC, whose vesicles contained DAF, MIRL, and CR1[86,87].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1981, when Miyakawa et al initially managed to demonstrate the diminished expression of Cregs, particularly that of CR1 (C3b receptor), on red-cell membrane of patients with SLE [ 79 ], several flow-cytometric and immunofluorescence studies have evaluated the presence of DAF and MIRL on erythrocytes in autoimmune diseases like SLE [ 59 , 60 , 63 65 ] and RA [ 67 , 68 ], without determining a specific pattern of the expression of these antigens. Primarily performed on a small sample of patients, they revealed a significant deficiency of these molecules – either jointly or separately – on RBCs, although without association with complement activity, the presence of anemia or antiphospholipid antibodies (aPLA) and clinical status [ 61 , 63 65 , 68 ].…”
Section: Discussionmentioning
confidence: 99%